Management of forgotten double J stents: insight from a systematic review of case reports - Antonius Galih Pranesdha Putra; Yufi Aulia Azmi; Soetojo Wirjopranoto; Nadya Rahmatika; Agustin Junior Nanda De Niro; Alviano Satria Wibawa; Kevin Muliawan Soetanto (Archivio Italiano di Urologia e Andrologia)
Background: Double J Stent is one of the procedures frequently performed in the field of urology. Forgotten DJ Stent is a problem that can cause serious complications. This systematic review aims to explore complications and management of patients with forgotten double J stents. Methods: Scientific literature was obtained from PubMed, ScienceDirect, and Google Scholar with a publication year limited to 2013-2023. The search string included ‘forgotten DJ stent, case report, complication’. Inclusion criteria were as follows: (1) case report or series, (2) available individual patient data, and (3) English language. Data are presented descriptively. Results: Of the 210 records, 14 articles published were analyzed after the full-text assessment. Forgotten DJ stent sufferers vary from age 7 years to 88 years. Male gender was predominant. The initial symptoms were flank pain and micturition disorders. The complications experienced were encrustation, multiple stones formation, emphysematous pyelonephritis, emphysematous perinephric abscess, fragmentation, and vesical calculus. In management, it was found that procedures were selected according to patient's situation at that time and the condition of the stent. There are case reports that report management that differed from those initially planned. All the patients were alive after treatment. Conclusions: A forgotten DJ stent can have serious consequences. The management approach requires a combination of various endourological procedures. In consideration of potential complications, urologists need to be careful in making decisions about the choice of technique used